Testing the phylogenetic affinities of Southeast Asia’s rarest geckos: Flap-legged geckos (Luperosaurus), Flying geckos (Ptychozoon) and their relationship to the pan-Asian genus Gekko - Brown, Rafe M.; Siler, Cameron D.; Das, I.; Yong, Min (Elsevier Ltd, 2012)
Some of Southeast Asia’s most poorly known vertebrates include forest lizards that are rarely seen by field biologists. Arguably the most enigmatic of forest lizards from the Indo Australian archipelago are the Flap-legged geckos and the Flying geckos of the genera Luperosaurus and Ptychozoon. As new species have accumulated, several have been noted for their bizarre combination of morphological characteristics, seemingly intermediate between these genera and the pan-Asian gecko genus Gekko. We used the first multilocus phylogeny for these taxa to estimate their relationships, with particular attention to the phylogenetic placement of the morphologically intermediate taxa Ptychozoon rhacophorus, Luperosaurus iskandari, and L. gulat. Surprisingly, our results demonstrate that Luperosaurus is more closely related to Lepidodactylus and Pseudogekko than it is to Gekko but that some species currently classified as Luperosaurus are nested within Gekko. The Flying Gecko genus Ptychozoon is also nested within Gekko, suggesting that higher-level taxonomic revision of the generic boundaries within Southeast Asian gekkonines will be a priority for the immediate future